The Role of Norepinephrine in Differential Response to Stress in an Animal Model of Posttraumatic Stress Disorder - Olson, Valerie G. (2011)
BACKGROUND: Posttraumatic stress disorder (PTSD) is a prevalent psychiatric disorder precipitated by exposure to extreme traumatic stress. Yet, most individuals exposed to traumatic stress do not develop PTSD and may be considered psychologically resilient. The neural circuits involved in susceptibility or resiliency to PTSD remain unclear, but clinical evidence implicates changes in the noradrenergic system. METHODS: An animal model of PTSD called Traumatic Experience with Reminders of Stress (TERS) was developed by exposing C57BL/6 mice to a single shock (2mA, 10sec) followed by exposure to six contextual1-minute reminders of the shock overa 25-dayperiod. Acoustic startle response (ASR) testing before the shock and after the last reminder allowed experimenters to separate the shocked mice into two cohorts: mice that developed a greatly increased ASR (TERS-susceptible mice) and mice that did not (TERS-resilient mice). RESULTS: Aggressive and social behavioral correlates of PTSD increased in TERS-susceptible mice but not in TERS-resilient mice or control mice. Characterization of c-Fos expression in stress-related brain regions revealed that TERS-susceptible and TERS-resilient mice displayed divergent brain activation following swim stress compared with control mice. Pharmacological activation of noradrenergic inhibitory autoreceptors or blockade of postsynaptic α(1)-adrenoreceptors normalized ASR, aggression, and social interaction in TERS-susceptible mice. The TERS-resilient, but not TERS-susceptible, mice showed a trend toward decreased behavioral responsiveness to noradrenergic autoreceptor blockade compared with control mice. CONCLUSIONS: These data implicate the noradrenergic system as a possible site of pathological and perhaps also adaptive plasticity in response to traumatic stress.